Radon-222 monitoring at German ICOS atmosphere stations - Gachkivskyi, Maksym; Karstens, Ute; Fischer, Bernd; Kubistin, Dagmar; Müller-Williams, Jennifer; Lindauer, Matthias; Levin, Ingeborg (Earth system science data, 2025)
Atmospheric measurements of the short-lived radioactive noble gas radon-222 (222Rn) have many applications. Its concentrations are driven by atmospheric mixing as well as seasonal variations, which follow the seasonality of 222Rn exhalation from continental soils, with lower values during the wet winter and spring months compared to more dry summer conditions. Hence, it can be used as a tracer to distinguish marine from continental air masses or for transport model validation. The Heidelberg Radon Monitor (HRM) is a static filter detector measuring atmospheric 214polonium (214Po), which is a progeny of 222Rn. These measurements can be used to infer atmospheric 222Rn activity concentrations if the radioactive disequilibrium between 214Po and 222Rn at the measurement site is known. In this study, 214Po activity concentrations measured with the HRM at eight stations in the Integrated Carbon Observation System (ICOS) Germany network are presented, along with guidelines for evaluating these data to estimate atmospheric 222Rn activity concentrations. In addition to the established line loss and disequilibrium corrections applied when sampling through long tubing or from air intake heights close to the ground, respectively, an upper limit for relative humidity (RH) is suggested, where secular equilibrium can still be assumed. At higher RH, aerosol scavenging effects can cause disequilibrium between 214Po and 222Rn. Using comparison with the model this threshold is determined to be at about 98 % RH and was applied uniformly at all measurement sites. A clear diurnal cycle of 222Rn is observed at all German tower stations during the summer and autumn months as is a seasonal cycle with a maximum during summer and autumn months. Overall, our results demonstrate that the 214Po-based 222Rn measurements with the HRM are reliable if the equilibrium conditions between 214Po and 222Rn can be ensured, i.e., for air intake heights above 80-90 ma.g.l. during conditions with RH<98 %. The corrected and ready-to-use dataset of 10-year radon activity concentrations from the eight ICOS stations is published alongside this paper (https://doi.org/10.18160/Q2M8-B1HJ, Fischer et al., 2024).